2002
DOI: 10.1097/00130478-200201000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Soluble intercellular cell adhesion molecule-1 and L-selectin plasma concentrations and response to surfactant in preterm infants

Abstract: In preterm infants with respiratory distress, a poor response to surfactant within 6 hrs of administration is associated with elevated circulating ICAM-1 concentrations at 24 hrs of age. Low plasma L-selectin at 24 hrs of age predicts prolonged requirement for supplemental oxygen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…L-Selectin is a cell surface adhesion molecule but can simultaneously be released as a soluble isoform, which reduces leukocyte adhesion to the endothelium, thereby ameliorating immune cell infiltration during inflammation (24). Of note, low L-selectin plasma level13hr have been associated with a poor responsiveness to surfactant therapy in preterm infants with respiratory distress and can serve as a predictive marker of a prolonged requirement for supplemental oxygen (25).…”
Section: Discussionmentioning
confidence: 99%
“…L-Selectin is a cell surface adhesion molecule but can simultaneously be released as a soluble isoform, which reduces leukocyte adhesion to the endothelium, thereby ameliorating immune cell infiltration during inflammation (24). Of note, low L-selectin plasma level13hr have been associated with a poor responsiveness to surfactant therapy in preterm infants with respiratory distress and can serve as a predictive marker of a prolonged requirement for supplemental oxygen (25).…”
Section: Discussionmentioning
confidence: 99%
“…24 Of note, low L-selectin plasma level have been associated with a poor responsiveness to surfactant therapy in preterm infants with respiratory distress and can serve as a predictive marker of a prolonged requirement for supplemental oxygen. 25 According to our results, L-selectin induction was correlated with preterm gestation age ( Table 2). Contrarily to the beneficial induction of ORM, SAP, PI16, and Lselectin in 36-PMA collected samples, we found that the concentration of leucine-rich alpha-2-glycoprotein (LRG1) increased over time (Table 2).…”
Section: Discussionmentioning
confidence: 63%
“…High E‐selectin levels in cord and peripheral blood [22, 23] have been shown to be predictive of BPD. Low plasma L‐selectin levels during the early postnatal period have been shown to be predictive of length of supplemental oxygen requirement [24] and risk of BPD [25, 26]. Dexamethasone treatment may also affect BPD risk through its impact on L‐selectin expression [27].…”
Section: Discussionmentioning
confidence: 99%